Pelaksanaan Program Pembelajaran Berbasis Proyek (PjBL) di Sekolah Menengah - Fitriani, Afifah; Febita, Disyah; Sari, Kiki Widya; Anggraini, R.A. Lia; Rosa, Raynisa Gildasa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Secondary education is required to equip students with 21st-century competencies through student-centered leraning approaches. One instructional model considered relevant to these demands is Project-Based Learning (PjBL). Although the effectiveness of PjBL on learning outcomes has been widely examined, studies that comprehensively describe its implementation ini secondary schools, particularly from an educational management perspective, remain limited. This study aims to analyze and synthesize research findings related to the implementation of PjBL ini secondary education, focusing on planning, organizing, implementation, evalutation, as well as supporting and inhibiting factors. This study employed a qualitative approach using a literature review method, analyzing relevant national accredited and internationally reputable journal articles published within the last five years. The findings indicate that successful PjBL implementation is determined by systematic project planning, effective learning organization, the teacher’s role as a facilitator, and the application of continuous authentic assessment. Key supporting factors include teachers pedagogical competence and school management support, while limited instructional time and variations in teachers understanding of PjBL remain major challenges. Therefore, the implementation of PjBL in secondary schools requires well planned and sustainable instructional management to escure and consistent practice.